Integration of concepts in the context of technical teaching integrated to high school from Potentially Meaningful Teaching Units (PMTU) (Research, Society and Development, 2020)
This work aims to present a proposal for a Potentially Meaningful Teaching Unit (PMTU) of Hydrostatic topics, in a perspective that enables the integration of contextualized physics concepts with the technical area of agriculture. The structure of the work brings, in addition to a brief report about the process of construction of the instructional material, an adaptation of the steps suggested by Marco Antonio Moreira (Moreira, 2011), fragmenting the stages of externalization of previous knowledge and which contemplate situations at an introductory and intermediate level, enabling greater detail specific topics and the progressive differentiation of concepts and, converging again to contemplate the principles of integrative reconciliation of UEPS concepts and evaluation. It also includes pedagogical and methodological principles that underlie the stages of UEPS, with emphasis on Ausubel's Theory of Meaningful Learning. Although the instructional material has been implemented in the educational context for which it is intended, this work does not intend to present results in relation to students' learning during the process of pedagogical intervention. The results are limited to the description of the elaboration process and the detailed result of this construction: the Hydrostatic PMTU.